The Impact of Financial Aid on Learning, Career Decisions, and Employment - Yang, Po (Chinese Education & Society, 2011)
China established a large-scale financial aid system in the late 1980s. This multilayered aid system aimed at enhancing educational and employment opportunities. However, very few studies have examined the impact of student aid on learning effort and outcome, career decisions, and early labor market performance. Using two recent Chinese college student surveys, this study found that students who received financial aid were significantly more likely to take more courses, spend more hours studying outside class, have a higher class ranking, and be less likely to fail a course. Additionally, having financial aid could promote graduate school enrollment and initial employment but had no significant impact on expected salary. Current aid programs for those who receive public financial assistance are thus beneficial in terms of educational outcome and employment perspective.
Keywords: Evidence; Outcomes of Education; Labor Market; Student Surveys; Foreign Countries; Employment Opportunities; Student Financial Aid; College Students; Educational Opportunities; Program Effectiveness